2022
DOI: 10.1177/10901981221098373
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Persons With Type 2 Diabetes Toward Diabetes Self-Management: A Qualitative Study

Abstract: Background. The global increase in type 2 diabetes (T2D) poses a significant public health challenge worldwide. Due to the chronic and complex nature of the disease, management does not depend on pharmacotherapy alone; rather, a comprehensive medical and self-management plan is required. Diabetes Self-Management Education programs should address diabetes-specific behaviors and be grounded in patients’ perceptions of their disease and its consequences. Aim. The study aims to understand perceptions of diabetes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…For example, the participants facilitated social support by encouraging family participation. Like this study, others have reported both supportive and discouraging effects of family involvement in diabetes management in Africa, and other parts of the world ( Abdulrehman et al, 2019 ; Bross et al, 2022 ; Chepulis et al, 2021 ; Mogre et al, 2019 ; Othman et al, 2022 ; Suglo, & Evans, 2020 ; Werfalli et al, 2020 ), necessitating the need for not only involving families in patient education but also educating them on how to prevent diabetes for themselves, as well as how to support a family member living with diabetes ( Thirsk & Schick-Makaroff, 2021 ).…”
Section: Discussionmentioning
confidence: 67%
“…For example, the participants facilitated social support by encouraging family participation. Like this study, others have reported both supportive and discouraging effects of family involvement in diabetes management in Africa, and other parts of the world ( Abdulrehman et al, 2019 ; Bross et al, 2022 ; Chepulis et al, 2021 ; Mogre et al, 2019 ; Othman et al, 2022 ; Suglo, & Evans, 2020 ; Werfalli et al, 2020 ), necessitating the need for not only involving families in patient education but also educating them on how to prevent diabetes for themselves, as well as how to support a family member living with diabetes ( Thirsk & Schick-Makaroff, 2021 ).…”
Section: Discussionmentioning
confidence: 67%
“…Barriers to DSM have been reported extensively in the literature. Locally, in Qatar, a qualitative study shed light on the barriers reported by 29 participants with diabetes [ 24 ]. The authors found similar barriers reported in other studies, such as work-related stress, the cost of testing strips, and long working hours; all external barriers.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found similar barriers reported in other studies, such as work-related stress, the cost of testing strips, and long working hours; all external barriers. However, with Qatar being a country that hosts 94 other nationalities, culture also plays a major role in how individuals with diabetes perceive their DSM [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who self-reported that they were married were coded as present on home social connectedness whereas patients who self-reported as single, divorced, or widowed were coded as absent on home social connectedness. Second, we operationalized workplace social connectedness as employment status since workplace structure and coworker social support impact self-management behavior (Bose, 2013; Loerbroks et al, 2018; McCarthy et al, 2021; Othman et al, 2022; Sarkar et al, 2016). Patients who reported working part time, working full time, or as a student were coded as present on workplace social connectedness.…”
Section: Methodsmentioning
confidence: 99%
“…For individuals who are physically present in the workforce, workplace structure and coworker social support can positively impact self-management behavior (Bose, 2013; McCarthy et al, 2021; Sarkar et al, 2016). While at work, patients living with diabetes report structural factors of the workplace as barriers to self-management, including nonroutine work, irregular working hours, and reduced access to healthy food (Loerbroks et al, 2018; Othman et al, 2022).…”
mentioning
confidence: 99%